Teachers’ Practices of Critical Thinking in the Algerian Secondary School EFL Classroom - Djouima, Leila (Journal of Human Sciences, 2020)
Critical thinking (CT) is unanimously considered to play a pivotal role in individuals’ academic life. This paper investigates the teachers’ practices of CT in the Algerian EFL secondary school classroom. It aims mainly at examining the teachers ‘implementation of CT through two procedures: Socratic questioning and Bloom’s taxonomy, hypothesizing that if teachers use Socratic Questioning and Bloom’s Taxonomy, CT would be implemented and learners’ CT skills would be fostered. To fulfill the purpose of this study, a questionnaire is administered to 20 secondary school teachers. The results revealed the teachers’ awareness of the importance of CT skills and the effectiveness of using Socratic Questioning and Bloom’s Taxonomy in fostering CT in EFL classroom despite the absence of a guiding and motivating. framework for its implementation.